2017
DOI: 10.12659/msm.898406
|View full text |Cite
|
Sign up to set email alerts
|

A Variant in the Precursor of MicroRNA-146a is Responsible for Development of Erectile Dysfunction in Patients with Chronic Prostatitis via Targeting NOS1

Abstract: BackgroundThe morbidity of erectile dysfunction (ED) has been found to be substantially increased in patients with chronic prostatitis (CP). Accumulating evidence shows that single-nucleotide polymorphism (SNP) located in pre-miRNA or mature microRNA may affect the processing of microRNA (miRNA) and alter the expression of the miRNA, as well as its target gene. In this study we investigated the association between rs2910164 G/C polymorphism and risk of ED in patients with CP, as well as the underlying molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It has been confirmed that nitric oxide synthase 1 (NOS1) is the target gene of miR-146a. By real-time PCR and Western blot analysis, it was found that the risk of erectile dysfunction in patients with CP who are carriers of miR-146a rs2910164 C allele was significantly decreased, which may be due to its ability to compromise the expression of miR-146a, and increase the expression of NOS1 (Ding et al 2017). miR-96 governs androgen signalling and prostate cancer progression by regulating RARc signal axis (Long et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that nitric oxide synthase 1 (NOS1) is the target gene of miR-146a. By real-time PCR and Western blot analysis, it was found that the risk of erectile dysfunction in patients with CP who are carriers of miR-146a rs2910164 C allele was significantly decreased, which may be due to its ability to compromise the expression of miR-146a, and increase the expression of NOS1 (Ding et al 2017). miR-96 governs androgen signalling and prostate cancer progression by regulating RARc signal axis (Long et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of miRNAs in the human genome is less than that of protein-coding genes, they are believed to regulate more than half of the human RNAs. miRNAs play an immunoregulatory role by regulating the expression of the immune regulatory genes, which is a new direction of immunology research in recent years (Ding et al 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can regulate gene expression through a complete or incomplete pairing of their seed sequences with the 3 'untranslated region (3'UTR) of their target genes, which can degrade the mRNA of target genes or suppress the translation of target genes [33,34]. For example, Ding et al [35] found that inhibiting miR-146a up-regulated NOS1, which reduced the incidence of erectile dysfunction in patients with CP. In addition, Wang et al [30] found that up-regulation of miR-141 regulated Keap/ Nrf2 signaling pathway, and reduced the expression of COX-2, the value of locomotion score, eye score, average inflammatory cell count, improving prostatitis.…”
Section: Case Discussionmentioning
confidence: 99%
“…The different 5'-UTRs of the multiple NOS1-mRNA isoforms (see above) are likely to regulate the translatability of these different NOS1 mRNAs [16]. Several miRNAs have been shown to directly [46][47][48][49][50][51] or indirectly [52] modulate human NOS1 expression.…”
Section: Post-transcriptional Regulation Of the Nos1 Expressionmentioning
confidence: 99%